PENGARUH KEPUTUSAN INVESTASI DAN KEPUTUSAN PENDANAAN TERHADAP NILAI PERUSAHAAN (STUDI KASUS PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2017) - Erin Mastura; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThe purpose of this research is to know the influence of investment decisions and funding decisions on the company's value in the manufacturing company sub-sector of food and beverage listed on the Indonesia Stock Exchange in 2015-2017, which is as much as 18 companies. Selection of samples using purposive sampling where samples were taken based on certain criteria, thus obtained as many as 16 food and beverage manufacturing companies listed on the Indonesia Stock Exchange in 2015-2017. The data analysis techniques in this study used the normality test, classic assumption test, multiple linear regression tests and hypotheses testing. Measuring instrument used to measure investment decision is Price Earning Ratio (PER), for funding decision is Debt to Equity Ratio (DER), and for company value is Price to book value (PBV). The results of this study show that the investment decisions positively and significantly affect the value of the company and the funding decisions are negatively and insignificant to the value of the company. Keywords: investment decisions, funding decisions, and corporate values